Adhesive composition for battery separator, slurry, separator and lithium ion battery
Modified polymer microsphere particles are prepared by adding surface polymer free volume modifier and affinity monomer to the battery separator bonding composition, which solves the problem of insufficient adhesion in dry and wet states in the prior art, and achieves stronger adhesion and better battery performance.
Patent Information
- Application Number
- CN202411353867.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing battery separator adhesive cannot take into account both the strong adhesive force in both the dry and wet states, resulting in the coating film being easily adhered or powdered, affecting the production efficiency and quality of the battery.
Uniform polymer microsphere particles are prepared by radical polymerization by adding surface polymer free volume modifier and affinity monomer to the bonding composition, modifying their surfaces and enhancing the interaction force with the pole sheet and the coating.
It improves the adhesion of the battery separator in the dry and wet states, avoids the phenomenon of coating powder loss, and enhances the electrochemical performance and production efficiency of the battery.
Smart Images

Figure 2D5AFDX5E8PTPOIVPOE5FR7XO3358KVP7AOYDMGR 
Figure AYQAV2SOEGJHEY8QMFTU1TWG9ZDLP8NJV7YBBBYS 
Figure DFCXLRP6LQMBS0AXIHFDPFMZSAGGAFYQBD6DDMFI
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to an adhesive composition for battery separators, a slurry, a separator and a lithium-ion battery. Background Art
[0002] In the fast charging technology of batteries, electrolyte, binder and diaphragm are key factors. The diaphragm separates the positive and negative electrodes to prevent short circuits, and optimized design can improve safety and charging performance. The performance of the diaphragm determines the internal resistance and interface structure of the battery, which in turn determines key characteristics such as battery capacity, charge and discharge current density and cycle performance. The diaphragm must have good electronic insulation and isolation, and at the same time have a certain pore size to ensure good penetration of lithium ions. The binder is formed on the diaphragm and is used to fix the pole pieces and electrolyte. Improving performance can improve battery stability and charging speed. The binder contains polymer microspheres, which serve as an isolation layer between the positive and negative pole pieces in lithium-ion batteries to prevent direct contact between the positive and negative pole pieces, thereby avoiding short circuits and internal reactions.
[0003] Chinese invention patent publication No. CN117060010A discloses a narrow distribution diaphragm binder; Chinese invention patent publication No. CN115536781A discloses a large-diameter core-shell polymer particle prepared by an improved aqueous suspension polymerization and / or emulsion polymerization method; Chinese invention patent publication No. CN117673652A discloses a secondary particle for a diaphragm coating that is easy to disperse and has high viscosity strength; Chinese invention patent publication No. CN109983599A discloses a binder composition for a porous membrane of a non-aqueous secondary battery that can form a porous membrane with improved adhesion in an electrolyte, heat shrinkage resistance in an electrolyte, and anti-adhesion properties.
[0004] However, most of the existing technologies, including the above-mentioned technical solutions, focus on improving the adhesion between the diaphragm and the electrode in the absence of electrolyte and preventing the coating from falling off. The microsphere adhesive used for diaphragm coating still has the problem that the adhesion in dry state and wet state cannot be taken into account:
[0005] (1) The adhesion in the dry state is excellent, but the coated separator is rolled up and sticky, which greatly reduces the production efficiency and affects the quality of the coated film. Because the polymer microsphere particles have a lower softening temperature in the dry state, the molecular chain segments are more stretched, and the interaction between the polar groups in the microsphere particles and the components of the electrode increases. When it is close to room temperature, it shows a strong adhesion, but at the same time, the interaction with itself and the substrate is also enhanced, showing a mutual adhesion phenomenon.
[0006] (2) When the adhesion in wet state is met, the room temperature adhesion is poor, resulting in serious opening of the core during core manufacturing, serious misalignment between the diaphragm and the electrode, and the risk of the core being unable to enter the shell and the cell short circuit, which greatly reduces the product yield. Because polymer microsphere particles are greatly affected by temperature, polymer microsphere particles in the prior art have excellent room temperature adhesion, but the electrolyte swells greatly at high temperatures. Therefore, in wet state, due to the large swelling of the electrolyte, the microsphere particles absorb a large amount of electrolyte, resulting in the separation of the microsphere particles and the components of the electrode, and the interaction force is weakened; on the contrary, due to the large intermolecular force, the microsphere particles swell less in the electrolyte, but at the same time, the movement of the molecular chain segments is hindered, and the interaction force with the components of the electrode is weak when close to room temperature.
[0007] (3) The microsphere particle dispersion is easy to settle and agglomerate, and it is difficult to redisperse and apply. The surface tension of the hydrophobic PE or PP base film is large, making it difficult for the coated microspheres to spread on the surface, resulting in shrinkage holes. Summary of the invention
[0008] In order to solve the above-mentioned prior art problems, the present invention provides a bonding composition for battery separators, slurry, separator and lithium ion battery. The present invention prepares a polymer microsphere particle dispersion liquid with uniform particle size and surface modified by the surface polymer free volume modifier, i.e., the bonding composition, by adding a surface polymer free volume modifier and an affinity monomer through free radical polymerization, further improving the bonding force between the particle coating film and the pole piece in dry and wet states, solving the technical problems in the prior art that it is impossible to take into account strong bonding force in both dry and wet states, and the winding coating film is easy to stick and easy to fall off.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] In a first aspect, a bonding composition for a battery separator comprises polymer microspheres and a modifier, wherein the modifier is a macromolecular free volume modifier on the surface of the microspheres, and the modifier accounts for 0.5 to 16% of the weight of the dispersion medium; the polymer microspheres contain affinity monomers, and the affinity monomers account for 1 to 15% of the total weight of all monomers of the polymer microspheres.
[0011] In a second aspect, a slurry for a battery separator comprises the bonding composition according to the first aspect.
[0012] In a third aspect, a diaphragm is formed using the bonding composition of the first aspect or the slurry of the second aspect.
[0013] In a fourth aspect, a lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and the separator according to the third aspect, wherein the separator separates the positive electrode sheet from the negative electrode sheet.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] The inventors have conducted in-depth research for the purpose of solving the above problems. Then, the inventors have newly discovered that by introducing a surface polymer free volume modifier into the medium phase, an affinity monomer is added to the polymer microsphere so that the surface of the polymer microsphere has an affinity group, and the surface polymer free volume is affinity to the modifier through the affinity group to modify the polymer microsphere, which not only modifies and softens the surface polymer of the polymer microsphere, but also plays a viscosity and toughness effect, enhances the interaction between the particles and the components of the pole piece and the particles and the components of the coating, improves the adhesion of the coated diaphragm to the positive and negative pole pieces in dry and wet states, and avoids the phenomenon of coating powder falling off; at the same time, it also reduces the surface tension of the polymer microsphere particles, improves the dispersibility of the coating slurry, makes the modified particle slurry spread evenly on the surface of the base film, increases the contact sites between the protruding particles and the components of the pole piece, and further enhances the adhesion between the coating film and the pole piece. When applied, it can reduce the membrane coating load, increase the membrane permeability, reduce the internal resistance, and improve the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The SEM image of the microsphere particle suspension prepared in Example 1;
[0017] Figure 2 for Figure 1 A partial enlarged view of
[0018] Figure 3 The particle size distribution diagram of the microsphere particle suspension prepared in Example 1;
[0019] Figure 4 This is a scanning electron microscope (SEM) image of the microsphere particle suspension prepared in Comparative Example 6;
[0020] Figure 5 The particle size distribution diagram of the microsphere particle suspension prepared in Comparative Example 6;
[0021] Figure 6 This is a scanning electron microscope (SEM) image of the microsphere particle suspension prepared in Comparative Example 9;
[0022] Figure 7 for Figure 6 A partial enlarged view of
[0023] Figure 8 This is the particle size distribution diagram of the microsphere particle suspension prepared in Comparative Example 9. DETAILED DESCRIPTION
[0024] Hereinafter, embodiments of the present invention will be described in detail.
[0025] [Bonding composition for battery separator]
[0026] The adhesive composition for battery separator comprises polymer microspheres and a modifier, wherein the modifier is a microsphere surface high molecular free volume modifier. The polymer microspheres comprise affinity monomers, hard monomers, soft monomers and functional monomers.
[0027] The modifier accounts for 0.5-16% of the weight of the dispersion medium; the modifier is selected from at least one of benzyl alcohol, dichloroethylene, dichloroethane, acetonitrile, ethanol, propylene glycol, 1,3-butanediol, n-butanol, tert-butanol, n-pentanol, acetone, n-butane, chloroform, dibutyl phthalate, tricresyl phosphate, ethylene carbonate, butyl ether, diethylamine, ethyl ether, n-hexane, isopropyl ether, ethyl acetate and acetic acid.
[0028] In the present invention, free volume refers to the randomly distributed cavities between molecular segments in a polymer, which provide space for the activities of the molecular segments. The size, concentration and size distribution of free volume are important factors affecting the transport properties of atoms and molecules.
[0029] By introducing a surface polymer free volume modifier into the medium phase, an affinity monomer is added to the polymer microsphere so that the surface of the polymer microsphere has an affinity group. After the surface polymer free volume is modified by the affinity group, the surface polymer free volume of the polymer microsphere is modified, the surface polymer is softened, and the viscosity and toughening effect is achieved, and the interaction between the particles and the components of the pole piece and the particles and the components of the coating is enhanced, taking into account the strong adhesion between the coating film and the positive and negative pole pieces in the dry and wet states, and improving the adhesion between the coated diaphragm and the positive and negative pole pieces in the dry and wet states and avoiding the phenomenon of coating powder falling. Therefore, the membrane coating load can be reduced, the membrane permeability can be increased, the internal resistance can be reduced, and the electrochemical performance of the battery can be improved. By adding the above-mentioned surface polymer free volume modifier, the surface tension of the polymer microsphere particles is reduced, the dispersibility of the coating slurry is improved, the modified particle slurry is evenly spread on the surface of the base film, the contact sites of the protruding particles with the components of the pole piece are increased, and the adhesion between the coating film and the pole piece is further enhanced. By adding a surface polymer free volume modifier and carrying out free radical polymerization, a dispersion of polymer microspheres with uniform particle size and modified surface is prepared, thereby further improving the adhesion between the particle coating film and the pole piece in dry and wet states.
[0030] The dispersion medium can be deionized water or salt water, including but not limited to lithium salt, sodium salt, potassium salt, zinc salt, magnesium salt, aluminum salt, etc. The salt content in the salt water is not particularly limited, and preferably, the salt concentration in the salt water is controlled within 0.1 mol / L.
[0031] When the surface polymer free volume modifier content is less than 0.5%, the viscosity and toughening effects are insufficient, resulting in poor adhesion between the coating film and the electrode. When the surface polymer free volume modifier content exceeds 16%, the adhesion between the coating film and the electrode decreases instead. This is because when the surface polymer free volume modifier content exceeds a certain proportion, it affects the distribution of the microsphere particles, increases the particle size consistency coefficient σ, and widens the microsphere particle size distribution, resulting in a decrease in contact points with the electrode, a decrease in the adhesion between the coating film and the electrode, and an increase in permeability, internal resistance, and deterioration of the electrochemical performance.
[0032] Among them, the affinity monomer accounts for 1-15% of the total weight of all monomers of the polymer microspheres; the affinity monomer has at least one of carboxyl, hydroxyl and polyethylene glycol side groups, which can greatly improve the adhesion between the polymer microsphere coating film and the electrode.
[0033] Wherein, the carboxyl-containing affinity monomer is selected from at least one of methacrylic acid, itaconic acid, acrylic acid, crotonic acid and β-acryloxypropionic acid;
[0034] The hydroxyl-containing affinity monomer is selected from at least one of hydroxybutyl acrylate, hydroxybutyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate and 2-hydroxypropyl 2-acrylate;
[0035] The affinity monomer containing polyethylene glycol is selected from at least one of methoxy polyethylene glycol methacrylate, polyethylene glycol monomethyl ether acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polypropylene glycol diacrylate and polypropylene glycol dimethacrylate.
[0036] In the present invention, when the affinity monomer ratio is less than 1%, the interaction force between the coating film bonding microspheres and the components of the electrode is weak, and the adhesion between the coating film and the electrode is weak; when the affinity monomer ratio exceeds 15%, the affinity group has a strong interaction force with the components, and the adhesion between the diaphragm and the electrode is strong, but at the same time it causes the coating films to adhere to each other, and the air permeability of the coating film deteriorates, and the internal resistance of the battery increases.
[0037] Among them, the hard monomer (softening temperature is 25°C~150°C) is selected from at least one of methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, acrylonitrile, methacrylonitrile, vinyl acetate, styrene, n-butyl methacrylate, isobutyl methacrylate, tert-butyl acrylate, octadecyl acrylate, cyclohexyl methacrylate, isobornyl methacrylate, 2-phenoxyethyl acrylate, stearic methacrylate, tetrahydrofuran acrylate, isobornyl acrylate, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate and 4-tert-butylcyclohexyl acrylate.
[0038] Wherein, the soft monomer (softening temperature is between -100°C and 25°C) is selected from at least one of methyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, ethyl acrylate, n-octyl acrylate, isooctyl acrylate, dodecyl acrylate, amyl acrylate, n-hexyl acrylate, 2-hydroxypropyl methacrylate, heptyl acrylate, butyl methacrylate, lauryl methacrylate, n-octyl methacrylate, isooctyl methacrylate, hexyl methacrylate, lauric methacrylate, methoxy polyethylene glycol methacrylate, isodecyl methacrylate, ethoxyethoxyethyl acrylate, isodecyl acrylate, hydroxyethyl methacrylate phosphate, 2-ethylhexyl methacrylate, isononyl acrylate and propoxylated nonylphenol acrylate.
[0039] Wherein, the functional monomer is selected from at least one of acrylamide, N-vinyl pyrrolidone, sodium styrene sulfonate, 2-sulfonic acid ethyl methacrylate, N-(hydroxymethyl)acrylamide, N-(3-hydroxypropyl)acrylamide, N-(hydroxyethyl)acrylamide, N-(2-hydroxypropyl)methacrylamide, diacetone acrylamide, glycidyl methacrylate, vinyl siloxanes, phenyl glycidyl ether acrylate, divinylbenzene, ethylene glycol dimethacrylate, N-(isobutoxy)methacrylamide, diallyl phthalate, trimethylolpropane triacrylate, triallyl isocyanurate, allyl methacrylate, ethyl acetoacetate methacrylate, diethylene glycol diacrylate, N-ethylacrylamide, N-propylacrylamide, N-(butoxymethyl)acrylamide and N-butylacrylamide.
[0040] Preferably, the hard monomer accounts for 40% to 90% of the total weight of all monomers of the polymer microspheres, the soft monomer accounts for 4% to 40% of the total weight of all monomers of the polymer microspheres, and the functional monomer accounts for 1% to 20% of the total weight of all monomers of the polymer microspheres.
[0041] The softening temperature of the polymer microspheres is 30°C to 130°C. In the present invention, when the softening temperature of the polymer microsphere particles is lower than 30°C, the coating film has a strong adhesive force with the pole piece, the coating film air permeability value increases by 8.8%, and the diaphragm pores are significantly blocked, resulting in a decrease in the air permeability of the coating film, an increase in the internal resistance of the lithium-ion battery, and a deterioration in the battery cycle performance; when the softening temperature of the polymer microsphere particles is higher than 130°C, the coating film and the pole piece adhesive force decrease significantly, resulting in a deterioration in the lithium-ion battery cycle performance.
[0042] Among them, the volume average particle size of the polymer microspheres is 0.4μm~15μm. In the present invention, "volume average particle size" means the particle size with a cumulative volume of 50% calculated from the small particle size side in the particle size distribution (volume basis) determined using a laser diffraction method. In the present invention, when the particle size of the polymer microsphere particles is ≤0.4μm, the consistency of the particle size distribution of the polymer microsphere particles σ is small, and the adhesion between the coating film and the pole piece is greatly improved, but the permeability value of the coating film increases by >5%, indicating that the small particles obviously block the pores of the diaphragm, resulting in an increase in the internal resistance of the lithium-ion battery and deterioration of the electrochemical performance. When the particle size of the binder microsphere particles is >15μm, the consistency of the particle size of the polymer microsphere particles deteriorates, σ>0.3, the effective contact sites between the microsphere particles and the components of the pole piece are reduced, the adhesion between the coating film and the pole piece is significantly reduced, and the risk of pore blocking of the microsphere particle coating film increases, resulting in reduced permeability of the coating film, increased internal resistance of the lithium-ion battery, and deterioration of the electrochemical cycle performance.
[0043] [Preparation of Adhesive Composition for Battery Separator]
[0044] The bonding composition is prepared by polymerizing a monomer composition comprising the above-mentioned monomers and a modifier.
[0045] The monomer polymerization method is not particularly limited, and any one or more of solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, ionic polymerization, coordination polymerization, and ring-opening polymerization can be used. The emulsifier, dispersant, polymerization initiator, polymerization aid, etc. used in the polymerization can be those commonly used, and the amount used is also set to the amount commonly used.
[0046] Preferably, the polymerization initiator is selected from at least one of persulfates (such as sodium persulfate, potassium persulfate, ammonium persulfate, etc.), inorganic peroxides such as hydrogen peroxide, etc., redox systems (such as persulfate-thiosulfate), azo initiators (such as azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovaleronitrile, azobiscyclohexylcarbonitrile, dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid, etc.) and acyl peroxides (such as benzoyl peroxide, lauroyl peroxide), etc.
[0047] [Slurry for battery separator]
[0048] The slurry of the present invention is a composition for forming a separator layer, comprising the above-mentioned bonding composition, and optionally further containing functional particles and other components. The amounts of the functional particles and other components used are not particularly limited.
[0049] Functional particles, such as non-conductive particles, may be inorganic particles or organic particles. The inorganic particles or organic particles may be used alone or in combination of two or more.
[0050] The other components are not particularly limited as long as they do not have an adverse effect on the battery reaction in the battery. In addition, the types of other components can be one or more. Examples of other components include solvents, surfactants, wetting agents, leveling agents, dispersants, water-soluble or water-insoluble adhesive polymers, etc.
[0051] The preparation method of the above slurry is not particularly limited. It can be prepared by mixing the above components using a known mixing method. Such mixing can be carried out using a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, an attritor, an ultrasonic disperser, a homogenizer, a planetary mixer, and Filmix.
[0052] [Diaphragm]
[0053] The diaphragm includes a base film and a glue layer located on one side or both sides of the base film, wherein the glue layer is formed by forming a coating film with the slurry and then drying it.
[0054] The base film material is selected from at least one of polyethylene, polypropylene, polyimide and polyester.
[0055] The method of coating the subbing layer is not particularly limited, and examples thereof include a doctor blade method, a reverse roll coating method, a direct roll coating method, a gravure printing method, an extrusion method, and a brush coating method.
[0056] [Lithium-ion battery]
[0057] A lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator separates the positive electrode sheet from the negative electrode sheet.
[0058] The present invention is further described in detail below with reference to the embodiments.
[0059] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0060] Unless otherwise specified, the meanings of the terms in this specification are the same as those generally understood by those skilled in the art. However, if there is any conflict, the definitions in this specification shall prevail.
[0061] As used herein, "includes," "comprising," "including," "containing," "having," or other variations are intended to encompass non-exclusive inclusions, and no distinction is made between these terms. The term "comprising" means that other steps and ingredients that do not affect the end result may be added. The term "comprising" also includes the terms "consisting of" and "consisting essentially of." The compositions and methods / processes of the present invention comprise, consist of, and consist essentially of the essential elements and limitations described herein, as well as any additional or optional ingredients, components, steps, or limitations described herein.
[0062] All numerical values or expressions used in the specification and claims relating to component amounts, process conditions, etc. should be understood to be modified by "about" in all cases. All ranges relating to the same component or property include endpoints, which can be independently combined. Since these ranges are continuous, they include every numerical value between the minimum and maximum values. It should also be understood that any numerical range cited in the application is expected to include all subranges within the range.
[0063] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.
[0064] Example 1
[0065] [Preparation of bonding composition]
[0066] The specific steps of preparing the bonding composition are as follows:
[0067] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0068] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0069] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0070] 4) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0071] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0072] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0073] [Preparation of slurry]
[0074] 150 parts of deionized water and 7.5 parts of polyacrylate dispersant were fully dissolved, stirred at 500 rpm for 30 min, 67.5 parts of the above microsphere particle suspension were added, and stirred at 1000 rpm for 120 min to obtain the desired coating slurry.
[0075] [Preparation of diaphragm]
[0076] The coating slurry is uniformly coated on the surface of the base film by gravure roller coating or spray coating, and a microsphere coated diaphragm is obtained after drying.
[0077] [Preparation of positive electrode sheet]
[0078] Nickel-cobalt-manganese (NCM) ternary material, conductive agent carbon black, adhesive polyvinylidene fluoride (PVDF) and N-methylpyrrolidone are stirred and mixed evenly in a weight ratio of 97.34:28.86:2.7:1.1 to obtain a positive electrode slurry, and then the positive electrode slurry is evenly coated on the positive electrode collector, and then dried, cold pressed and cut to obtain a positive electrode sheet.
[0079] [Preparation of negative electrode sheet]
[0080] The active material artificial graphite, the conductive agent carbon black, the adhesive styrene-butadiene rubber (SBR) and the thickener sodium hydroxymethyl cellulose are dissolved in the solvent deionized water in a weight ratio of 96.2:0.8:0.8:1.2, and the negative electrode slurry is prepared after being evenly mixed; the negative electrode slurry is evenly coated on the negative electrode collector copper foil once or multiple times, and the negative electrode sheets are obtained after drying, cold pressing and cutting.
[0081] [Preparation of electrolyte]
[0082] In an argon atmosphere glove box, (H2O < 0.1ppm, O2 < 0.1ppm), organic solvent ethylene carbonate (EC) / ethyl methyl carbonate were mixed in a volume ratio of 3 / 7, 12.5% LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred evenly to obtain an electrolyte.
[0083] [Preparation of lithium-ion batteries]
[0084] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, the bare cell is welded with a pole ear, and the bare cell is transferred into an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of standing, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain the lithium-ion battery product of Example 1.
[0085] Example 2
[0086] Except for the step of preparing the bonding composition, other steps of Example 2 are the same as those of Example 1.
[0087] Example 2 The specific steps for preparing the bonding composition are as follows:
[0088] 1) Add 497.5 parts of deionized water, 2.5 parts of benzyl alcohol (surface polymer free volume modifier) and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0089] 2) 59 parts of styrene, 32 parts of ethyl acrylate, 7 parts of itaconic acid and 2 parts of N-ethylacrylamide were mixed and set aside;
[0090] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0091] 4) 33 parts of acrylonitrile, 28 parts of styrene, 30 parts of ethyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0092] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0093] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0094] Example 3
[0095] Except for the step of preparing the bonding composition, other steps of Example 3 are the same as those of Example 1.
[0096] Example 3 The specific steps for preparing the bonding composition are as follows:
[0097] 1) Add 485.55 parts of deionized water, 14.45 parts of surface polymer free volume modifier ethylene dichloride and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0098] 2) 38 parts of styrene, 23 parts of acrylonitrile, 30 parts of ethyl acrylate, 7 parts of crotonic acid and 2 parts of ethylene glycol dimethacrylate are mixed uniformly for later use;
[0099] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0100] 4) 65 parts of acrylonitrile, 26 parts of ethyl acrylate, 7 parts of acrylic acid and 2 parts of divinylbenzene are mixed uniformly for later use;
[0101] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0102] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0103] Example 4
[0104] Except for the step of preparing the bonding composition, other steps of Example 4 are the same as those of Example 1.
[0105] Example 4 The specific steps for preparing the bonding composition are as follows:
[0106] 1) Add 460.25 parts of deionized water, 39.75 parts of surface polymer free volume modifier ethylene dichloride and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0107] 2) 63 parts of methacrylonitrile, 28 parts of butyl acrylate, 7 parts of crotonic acid and 2 parts of divinylbenzene are mixed uniformly for later use;
[0108] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0109] 4) 31 parts of acrylonitrile, 30 parts of styrene, 30 parts of ethyl acrylate, 7 parts of poly(ethylene glycol) methacrylate and 2 parts of ethylene glycol dimethacrylate were mixed evenly for later use;
[0110] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0111] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0112] Example 5
[0113] Except for the step of preparing the bonding composition, other steps of Example 5 are the same as those of Example 1.
[0114] Example 5 The specific steps for preparing the bonding composition are as follows:
[0115] 1) Add 433.2 parts of deionized water, 66.8 parts of acetonitrile as a surface polymer free volume modifier and 1 part of sodium persulfate as an initiator into a reaction kettle and stir evenly;
[0116] 2) 63 parts of methacrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0117] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0118] 4) 38 parts of acrylonitrile, 23 parts of styrene, 30 parts of ethyl acrylate, 7 parts of hydroxybutyl methacrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0119] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0120] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0121] Example 6
[0122] Except for the step of preparing the bonding composition, other steps of Example 6 are the same as those of Example 1.
[0123] Example 6 The specific steps for preparing the bonding composition are as follows:
[0124] 1) Add 473.95 parts of deionized water, 26.05 parts of surface polymer free volume modifier ethanol and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0125] 2) 63 parts of methacrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0126] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0127] 4) 66 parts of acrylonitrile, 26 parts of ethyl acrylate, 7 parts of hydroxyethyl methacrylate and 2 parts of N-(butoxymethyl)acrylamide are mixed evenly for later use;
[0128] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0129] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0130] Example 7
[0131] Except for the step of preparing the bonding composition, other steps of Example 7 are the same as those of Example 1.
[0132] Example 7 The specific steps for preparing the bonding composition are as follows:
[0133] 1) Add 475.8 parts of deionized water, 24.2 parts of surface polymer free volume modifier n-hexane and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0134] 2) 66 parts of acrylonitrile, 26 parts of ethyl acrylate, 7 parts of β-hydroxypropyl acrylate and 2 parts of N-(butoxymethyl)acrylamide were mixed and set aside;
[0135] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0136] 4) 63 parts of methacrylonitrile, 28 parts of butyl acrylate, 7 parts of 4-hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0137] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0138] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0139] Example 8
[0140] Except for the step of preparing the bonding composition, other steps of Example 8 are the same as those of Example 1.
[0141] Example 8 The specific steps for preparing the bonding composition are as follows:
[0142] 1) Add 475.1 parts of deionized water, 24.9 parts of acetonitrile as a surface polymer free volume modifier and 1 part of sodium persulfate as an initiator into a reaction kettle and stir evenly;
[0143] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0144] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0145] 4) 59 parts of styrene, 32 parts of ethyl acrylate, 7 parts of hydroxyethyl acrylate and 2 parts of N-(butoxymethyl)acrylamide were mixed and set aside;
[0146] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0147] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0148] Example 9
[0149] Except for the step of preparing the bonding composition, other steps of Example 9 are the same as those of Example 1.
[0150] Example 9 The specific steps for preparing the bonding composition are as follows:
[0151] 1) Add 474.85 parts of deionized water, 25.15 parts of ethyl acetate (surface polymer free volume modifier) and 1 part of sodium persulfate (initiator) into a reactor and stir evenly;
[0152] 2) 59 parts of styrene, 32 parts of ethyl acrylate, 7 parts of 2-hydroxypropyl acrylate and 2 parts of N-(butoxymethyl)acrylamide were mixed and set aside;
[0153] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0154] 4) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of β-hydroxypropyl methacrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0155] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0156] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0157] Example 10
[0158] Except for the step of preparing the bonding composition, other steps of Example 10 are the same as those of Example 1.
[0159] Example 10 The specific steps for preparing the bonding composition are as follows:
[0160] 1) Add 474.15 parts of deionized water, 25.85 parts of surface polymer free volume modifier ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0161] 2) 63 parts of methacrylonitrile, 28 parts of butyl acrylate, 7 parts of polyethylene glycol diacrylate and 2 parts of divinyl benzene are mixed uniformly for later use;
[0162] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0163] 4) Mix 54 parts of styrene, 37 parts of isooctyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of N-ethylacrylamide and set aside;
[0164] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0165] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0166] Embodiment 11
[0167] Except for the step of preparing the bonding composition, other steps of Example 11 are the same as those of Example 1.
[0168] Example 11 The specific steps for preparing the bonding composition are as follows:
[0169] 1) Add 1052.2 parts of deionized water, 24.3 parts of surface polymer free volume modifier glycerol and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0170] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of polypropylene glycol diacrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0171] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0172] 4) 67 parts of styrene, 26 parts of ethyl acrylate and 7 parts of polypropylene glycol diacrylate are uniformly mixed and set aside;
[0173] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0174] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0175] Example 12
[0176] Except for the step of preparing the bonding composition, other steps of Example 12 are the same as those of Example 1.
[0177] Example 12 The specific steps for preparing the bonding composition are as follows:
[0178] 1) Add 292.3 parts of deionized water, 24.4 parts of surface polymer free volume modifier 1,3-butanediol and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0179] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0180] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0181] 4) Mix 65 parts of methacrylonitrile, 28 parts of butyl acrylate and 7 parts of hydroxybutyl acrylate evenly for later use;
[0182] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0183] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0184] Example 13
[0185] Except for the step of preparing the bonding composition, other steps of Example 13 are the same as those of Example 1.
[0186] Example 13 The specific steps for preparing the bonding composition are as follows:
[0187] 1) Add 207.6 parts of deionized water, 25.7 parts of surface polymer free volume modifier n-butanol and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0188] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0189] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0190] 4) 67 parts of acrylonitrile, 26 parts of ethyl acrylate and 7 parts of hydroxybutyl acrylate are mixed evenly for later use;
[0191] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0192] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0193] Embodiment 14
[0194] Except for the steps of preparing the bonding composition and the steps of preparing the slurry and the diaphragm, the other steps of Example 14 are the same as those of Example 1.
[0195] Example 14 The bonding composition was prepared by suspension polymerization, and the specific steps were as follows:
[0196] 1) Add 474.3 parts of deionized water, 25.7 parts of surface polymer free volume modifier tert-butyl alcohol and 1 part of polyvinyl alcohol into a reaction kettle and stir evenly;
[0197] 2) 133 parts of acrylonitrile, 56 parts of isooctyl methacrylate, 7 parts of hydroxybutyl acrylate, 4 parts of divinylbenzene and 1 part of benzoyl peroxide are mixed uniformly for later use;
[0198] 3) Add the solution of step 2) into the reactor of step 1), high-speed shear at 2000 rpm for 5 min, pass nitrogen for 30 min, and heat to 80°C for reaction for 5 h;
[0199] 4) After the reaction in step 3) is completed, the temperature is finally raised to 85°C and kept for 1 hour to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0200] 5) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0201] Preparation of slurry: 500 g of deionized water, 40 g of CMC dispersion with a solid content of 0.4%, 10 parts of polyacrylate dispersant and 10 parts of binder solution were stirred at 800 rpm for 20 min, 120 parts of ceramic powder were added, and the mixture was stirred at 1200 rpm for 30 min. Finally, 60 parts of the microsphere particle suspension of the present invention were added, and the mixture was stirred at 800 rpm for 30 min to obtain ceramic slurry.
[0202] Preparation of the diaphragm: The ceramic slurry is evenly coated on the surface of the base film by gravure roller coating, and after drying, a ceramic microsphere mixed coating diaphragm is obtained.
[0203] Embodiment 15
[0204] Except for the step of preparing the bonding composition, other steps of Example 15 are the same as those of Example 1.
[0205] Example 15 The bonding composition is prepared by dispersion polymerization, and the specific steps are as follows:
[0206] 1) Add 474.3 parts of sodium salt water, 25.7 parts of surface polymer free volume modifier n-pentanol and 1 part of polyvinyl pyrrolidone into a reaction kettle and stir evenly;
[0207] 2) 119 parts of styrene, 70 parts of butyl acrylate, 7 parts of β-acryloxypropionic acid, 4 parts of divinylbenzene and 1 part of benzoyl peroxide were mixed uniformly for later use;
[0208] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 75°C for 8 hours;
[0209] 4) After the reaction in step 3) is completed, the temperature is finally raised to 80°C and kept for 1 hour to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0210] 5) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0211] Example 16
[0212] Except for the step of preparing the bonding composition, other steps of Example 16 are the same as those of Example 1.
[0213] Example 16 The bonding composition is prepared by emulsion polymerization, and the specific steps are as follows:
[0214] 1) 474.3 parts of deionized water, 25.7 parts of surface polymer free volume modifier acetone, 63 parts of methacrylonitrile, 28 parts of isooctyl methacrylate, 7 parts of hydroxybutyl acrylate, 2 parts of ethylene glycol dimethacrylate, 1 part of sodium bicarbonate and 1 part of sodium dodecyl sulfate were emulsified at 1200 rpm and added into the reactor, mixed evenly, passed nitrogen for 30 minutes, and heated to 75°C for reaction for 2 hours;
[0215] 2) Add 1 part of initiator ammonium persulfate to react;
[0216] 3) 134 parts of acrylonitrile, 55 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate, 4 parts of ethylene glycol dimethacrylate and 2 parts of sodium lauryl sulfate were mixed uniformly by high-speed emulsification for later use;
[0217] 4) After reaction 1 is completed, the solution in step 3 is added to the reactor and reacted for 8 hours;
[0218] 5) After the reaction in step 4) is completed, the temperature is finally raised to 80°C and kept for 1 hour to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0219] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0220] Embodiment 17
[0221] Except for the step of preparing the bonding composition, other steps of Example 17 are the same as those of Example 1.
[0222] Example 17 The specific steps for preparing the bonding composition are as follows:
[0223] 1) Add 476.55 parts of deionized water, 23.45 parts of surface polymer free volume modifier n-butane and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0224] 2) 53 parts of styrene, 38 parts of butyl acrylate, 7 parts of methoxy polyethylene glycol methacrylate and 2 parts of divinyl benzene are mixed uniformly for later use;
[0225] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0226] 4) 26 parts of styrene, 27 parts of acrylonitrile, 38 parts of ethyl acrylate, 7 parts of methoxy polyethylene glycol methacrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0227] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0228] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0229] Embodiment 18
[0230] Except for the step of preparing the bonding composition, other steps of Example 18 are the same as those of Example 1.
[0231] Example 18 The specific steps for preparing the bonding composition are as follows:
[0232] 1) Add 475.75 parts of deionized water, 24.25 parts of chloroform (surface polymer free volume modifier) and 1 part of sodium persulfate (initiator) into a reaction kettle and stir evenly;
[0233] 2) 65 parts of acrylonitrile, 26 parts of ethyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of N-(butoxymethyl)acrylamide are mixed evenly for later use;
[0234] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0235] 4) 31 parts of styrene, 34 parts of acrylonitrile, 26 parts of ethyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0236] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0237] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0238] Embodiment 19
[0239] Except for the step of preparing the bonding composition, other steps of Example 19 are the same as those of Example 1.
[0240] Example 19 The specific steps for preparing the bonding composition are as follows:
[0241] 1) Add 473.25 parts of deionized water, 26.75 parts of surface polymer free volume modifier dibutyl phthalate and 1 part of initiator sodium persulfate into a reaction kettle and stir evenly;
[0242] 2) 78 parts of methacrylonitrile, 13 parts of isooctyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0243] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0244] 4) 78 parts of acrylonitrile, 13 parts of isooctyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of N-(butoxymethyl)acrylamide are mixed evenly for later use;
[0245] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0246] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0247] Embodiment 20
[0248] Except for the step of preparing the bonding composition, other steps of Example 20 are the same as those of Example 1.
[0249] Example 20 The specific steps for preparing the bonding composition are as follows:
[0250] 1) Add 474.15 parts of deionized water, 25.85 parts of surface polymer free volume modifier tricresyl phosphate and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0251] 2) 87 parts of acrylonitrile, 4 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of N-(butoxymethyl)acrylamide are mixed uniformly for later use;
[0252] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0253] 4) 85 parts of acrylonitrile, 6 parts of ethyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0254] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0255] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0256] Embodiment 21
[0257] Except for the step of preparing the bonding composition, other steps of Example 21 are the same as those of Example 1.
[0258] Example 21 The specific steps for preparing the bonding composition are as follows:
[0259] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier ethylene carbonate and 1 part of initiator sodium persulfate into a reaction kettle and stir evenly;
[0260] 2) 69 parts of acrylonitrile, 28 parts of butyl acrylate, 1 part of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0261] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0262] 4) 69 parts of acrylonitrile, 28 parts of butyl acrylate, 1 part of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0263] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0264] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0265] Embodiment 22
[0266] Except for the step of preparing the bonding composition, other steps of Example 22 are the same as those of Example 1.
[0267] Example 22 The specific steps for preparing the bonding composition are as follows:
[0268] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier butyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0269] 2) 66 parts of acrylonitrile, 28 parts of butyl acrylate, 4 parts of polypropylene glycol dimethacrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0270] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0271] 4) 66 parts of acrylonitrile, 28 parts of butyl acrylate, 4 parts of polypropylene glycol dimethacrylate and 2 parts of divinyl benzene are mixed uniformly for later use;
[0272] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0273] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0274] Embodiment 23
[0275] Except for the step of preparing the bonding composition, other steps of Example 23 are the same as those of Example 1.
[0276] Example 23 The specific steps for preparing the bonding composition are as follows:
[0277] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier diethylamine and 1 part of initiator sodium persulfate into a reaction kettle and stir evenly;
[0278] 2) 60 parts of acrylonitrile, 28 parts of butyl acrylate, 10 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0279] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0280] 4) 60 parts of acrylonitrile, 28 parts of butyl acrylate, 10 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0281] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0282] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0283] Embodiment 24
[0284] Except for the step of preparing the bonding composition, other steps of Example 24 are the same as those of Example 1.
[0285] Example 24 The specific steps for preparing the bonding composition are as follows:
[0286] 1) Add 475.05 parts of deionized water, 24.95 parts of acetic acid (surface polymer free volume modifier) and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0287] 2) 55 parts of acrylonitrile, 28 parts of butyl acrylate, 15 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0288] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0289] 4) 55 parts of acrylonitrile, 28 parts of butyl acrylate, 15 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0290] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0291] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0292] Embodiment 25
[0293] Except for the step of preparing the bonding composition, other steps of Example 25 are the same as those of Example 1.
[0294] Example 25 The specific steps for preparing the bonding composition are as follows:
[0295] 1) Add 475.05 parts of deionized water, 14.95 parts of isopropyl ether as a surface polymer free volume modifier, 10 parts of acetic acid as a surface polymer free volume modifier and 1 part of sodium persulfate as an initiator into a reaction kettle and stir evenly;
[0296] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of methacrylic acid and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0297] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0298] 4) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of methacrylic acid and 2 parts of divinylbenzene are mixed uniformly for later use;
[0299] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0300] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0301] Embodiment 26
[0302] Except for the step of preparing the bonding composition, other steps of Example 26 are the same as those of Example 1.
[0303] Example 26 The specific steps for preparing the bonding composition are as follows:
[0304] 1) Add 475.05 parts of deionized water, 12.95 parts of surface polymer free volume modifier isopropyl ether, 12 parts of surface polymer free volume modifier tricresyl phosphate and 1 part of initiator sodium persulfate into a reaction kettle and stir evenly;
[0305] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of polyethylene glycol monomethyl ether acrylate and 2 parts of ethylene glycol dimethacrylate are mixed uniformly for later use;
[0306] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0307] 4) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of polyethylene glycol monomethyl ether acrylate and 2 parts of divinyl benzene are mixed uniformly for later use;
[0308] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0309] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0310] Embodiment 27
[0311] Except for the step of preparing the bonding composition, other steps of Example 27 are the same as those of Example 1.
[0312] Example 27 The specific steps for preparing the bonding composition are as follows:
[0313] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0314] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 2 parts of polyethylene glycol monomethyl ether acrylate, 2 parts of acrylic acid, 3 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed uniformly for later use;
[0315] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0316] 4) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 2 parts of polyethylene glycol monomethyl ether acrylate, 2 parts of acrylic acid, 3 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0317] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0318] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0319] Comparative Example 1
[0320] Except for preparing the bonding composition by a one-step process, other steps of Comparative Example 1 are the same as those of Example 1.
[0321] The specific steps of preparing the bonding composition are as follows:
[0322] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0323] 2) 126 parts of styrene, 56 parts of butyl acrylate, 14 parts of hydroxybutyl acrylate, 2 parts of ethylene glycol dimethacrylate and 2 parts of divinyl benzene are mixed uniformly for later use;
[0324] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0325] 4) After the reaction in step 3) is completed, the temperature is finally raised to 75°C and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0326] 5) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0327] Comparative Example 2
[0328] Except for the step of preparing the bonding composition, other steps of Comparative Example 2 are the same as those of Example 1.
[0329] Comparative Example 2 The specific steps for preparing the bonding composition are as follows:
[0330] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0331] 2) 53 parts of acrylonitrile, 38 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed uniformly for later use;
[0332] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0333] 4) 49 parts of acrylonitrile, 42 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed uniformly for later use;
[0334] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0335] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0336] Comparative Example 3
[0337] Except for the step of preparing the bonding composition, other steps of Comparative Example 3 are the same as those of Example 1.
[0338] Comparative Example 3 The specific steps for preparing the bonding composition are as follows:
[0339] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0340] 2) 91 parts of acrylonitrile, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0341] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0342] 4) 91 parts of acrylonitrile, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0343] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0344] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0345] Comparative Example 4
[0346] Except for the step of preparing the bonding composition, other steps of Comparative Example 4 are the same as those of Example 1.
[0347] Comparative Example 4 The specific steps for preparing the bonding composition are as follows:
[0348] 1) Add 419.35 parts of deionized water, 80.65 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0349] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0350] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0351] 4) 63 parts of acrylonitrile, 32 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed uniformly for later use;
[0352] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0353] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0354] Comparative Example 5
[0355] Except for the step of preparing the bonding composition, other steps of Comparative Example 5 are the same as those of Example 1.
[0356] Comparative Example 5 The specific steps for preparing the bonding composition are as follows:
[0357] 1) Add 498.75 parts of deionized water, 1.25 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0358] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0359] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0360] 4) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed uniformly for later use;
[0361] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0362] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0363] Comparative Example 6
[0364] Comparative Example 6 The method for preparing the bonding composition is the same as that of Example 1, except that the surface polymer free volume modifier isopropyl ether is replaced by N-methylpyrrolidone.
[0365] Comparative Example 7
[0366] Comparative Example 7 The method for preparing the bonding composition is the same as that of Example 1, except that the surface polymer free volume modifier isopropyl ether is replaced by N,N-dimethylformamide.
[0367] Comparative Example 8
[0368] Comparative Example 8 The method for preparing the bonding composition is the same as that of Example 1, except that the surface polymer free volume modifier isopropyl ether is replaced by dimethyl sulfoxide.
[0369] Comparative Example 9
[0370] Except for the step of preparing the bonding composition, other steps of Comparative Example 9 are the same as those of Example 1.
[0371] Comparative Example 7 The specific steps for preparing the bonding composition are as follows:
[0372] 1) Add 2315 parts of deionized water, 23.95 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0373] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0374] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0375] 4) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0376] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0377] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0378] Comparative Example 10
[0379] Except for the step of preparing the bonding composition, other steps of Comparative Example 10 are the same as those of Example 1.
[0380] Comparative Example 10 The specific steps for preparing the bonding composition are as follows:
[0381] 1) Add 160.8 parts of deionized water, 24.9 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0382] 2) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0383] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0384] 4) 63 parts of acrylonitrile, 28 parts of butyl acrylate, 7 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0385] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0386] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0387] Comparative Example 11
[0388] Except for the step of preparing the bonding composition, other steps of Comparative Example 11 are the same as those of Example 1.
[0389] Comparative Example 11 The specific steps for preparing the bonding composition are as follows:
[0390] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0391] 2) 70 parts of acrylonitrile, 28 parts of butyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0392] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0393] 4) 70 parts of acrylonitrile, 28 parts of butyl acrylate and 2 parts of divinyl benzene are mixed uniformly for later use;
[0394] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0395] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0396] Comparative Example 12
[0397] Except for the step of preparing the bonding composition, other steps of Comparative Example 12 are the same as those of Example 1.
[0398] Comparative Example 12 The specific steps for preparing the bonding composition are as follows:
[0399] 1) Add 475.05 parts of deionized water, 24.95 parts of surface polymer free volume modifier isopropyl ether and 1 part of initiator sodium persulfate into a reactor and stir evenly;
[0400] 2) 52 parts of acrylonitrile, 28 parts of butyl acrylate, 18 parts of hydroxybutyl acrylate and 2 parts of ethylene glycol dimethacrylate are mixed evenly for later use;
[0401] 3) Add the solution of step 2) into the reactor of step 1), pass nitrogen for 30 minutes, and heat to 70°C for reaction for 5 hours;
[0402] 4) 52 parts of acrylonitrile, 28 parts of butyl acrylate, 18 parts of hydroxybutyl acrylate and 2 parts of divinylbenzene are mixed uniformly for later use;
[0403] 5) After the reaction of step 3) is completed, the solution of step 4) is continuously dripped into the reaction system for 8 hours, and finally the temperature is raised to 75° C. and kept for 2 hours to obtain a polymer microsphere dispersion with modified surface polymer free volume;
[0404] 6) The polymer microsphere dispersion prepared above is neutralized with a 1% lithium hydroxide aqueous solution to a pH of 6-8 to obtain a lithiated microsphere particle suspension.
[0405] Comparative Example 13
[0406] Comparative Example 13 The bonding composition is prepared in the same manner as in Example 1, except that the affinity monomer is selected from 2-acrylamide-2-methylpropanesulfonic acid.
[0407] In the embodiments and comparative examples, the softening temperature, volume average particle size and particle size consistency of the polymer microspheres, the air permeability and hot and cold adhesion, wet adhesion of the coating film, the current internal resistance DCR and capacity retention rate of the battery were measured and evaluated using the following methods, respectively. The test results are shown in Table 1 below.
[0408] <Softening temperature>
[0409] The softening temperature of the polymer microspheres was measured using a differential scanning calorimeter as follows:
[0410] (1) Prepare samples and reference materials;
[0411] (2) Place the sample and reference in the two heat pools of the instrument respectively. The specific test process is described as follows: 1. Under (nitrogen) atmosphere, the initial equilibrium temperature is (25) °C; 2. Heat to (120) °C at a rate of (5) °C / min; if necessary, keep warm at (120) °C for (30) min; 3. Cool to (-50) °C at (5) °C / min, and then heat to (200) °C at (5) °C / min;
[0412] (3) Start the equipment and record the curve of heat flow changing with temperature;
[0413] (4) Observe the step change in the curve. This point is the softening temperature.
[0414] <Volume average particle size>
[0415] The volume average particle size of polymer microspheres was measured using Malvern Mastersizer 2000 laser particle size analyzer. Reference standard process: GB / T19077-2016 / ISO 13320:2009, specific test process: take an appropriate amount of the sample to be tested (the sample concentration is guaranteed to be 8-12% shading), add 20ml DIW, and simultaneously supercharge for 5 minutes (53KHz / 120w) to ensure that the sample is completely dispersed, and then measure the sample according to GB / T19077-2016 / ISO 13320:2009 standard.
[0416] <Particle size consistency>
[0417] The specific calculation formula for particle size consistency σ is: ; Here, d(x,0.5) is the median particle size distribution (where x quilt v , s , l or n replace), d i and X i are the average diameter, i It is the particle size grade and can be measured by Malvern Mastersizer 3000.
[0418] <Coating film air permeability>
[0419] The air permeability of the coating film is measured by Wangyan air permeability tester EG01-55-1MR, using the principle of differential pressure method, as follows: In an environment with a humidity of 40RH% and a temperature of 25℃, the test specimen is placed between the upper and lower test chambers and clamped and sealed. The air permeability of the specimen is calculated based on the time required for the specimen to pass through 100ml of gas with an area of 6.45cm2 under a pressure difference of 1.21kpa. Ten data are tested for each sample and the average value is taken.
[0420] <Hot and cold adhesion of coating film>
[0421] Cold pressed electrode sample: The prepared negative electrode and microsphere coated diaphragm are pressed together according to the production line standard. The conditions are: room temperature -7MPa-15s. The cold pressing of the positive electrode and microsphere diaphragm is the same as above.
[0422] Hot pressing of electrode samples: The prepared negative electrode and microsphere coated separator are pressed together according to the production line standard, the conditions are: 70-3MPa-3s, and the hot pressing of the positive electrode and microsphere separator is the same as above.
[0423] Adhesion test: Referring to the national standard GBT-2790-1995 [Adhesive 180° Peel Strength Test Method], the adhesion test process of the embodiments and comparative examples of the present application is as follows: Use a blade to cut a cold-pressed electrode (including electrode and diaphragm) sample with a width of 30mm and a length of 100-160mm, and stick a special double-sided tape on the steel plate. The tape has a width of 20mm and a length of 90-150mm. Stick the cold-pressed electrode sample cut earlier on the double-sided tape, insert a paper tape with a width equal to the electrode pattern and a length of 250mm under the diaphragm, and fix it with wrinkled glue. Turn on the power of the Sansi tensile testing machine (sensitivity is 1N), the indicator light is on, adjust the limit block to the appropriate position, and fix the end of the steel plate without the electrode sample with the lower clamp. Fold the paper tape upwards and fix it with the upper clamp. Use the "up" and "down" buttons on the manual controller attached to the tensile testing machine to adjust the position of the upper clamp. Then conduct the test and read the value. The force when the electrode and diaphragm are peeled off and balanced is divided by the width of the tape as the unit of adhesion of the electrode to characterize the adhesion strength between the electrode and the diaphragm.
[0424] <Wet Adhesion>
[0425] Inject 1 ml of electrolyte into the hot pressed electrode sample to allow the electrolyte to fully soak the interface between the coating film and the electrode. Then place it in a sealed bag at 60°C for 12 hours. After soaking, use the above-mentioned adhesion test method to test the adhesion in a wet state.
[0426] <Battery Performance Test>
[0427] Taking Example 1 as an example, the battery DC impedance test process is as follows: At 25°C, the battery corresponding to Example 1 is charged to 4.35V at a constant current of 1 / 3, and then charged to a current of 0.05C at a constant voltage of 4.35V. After standing for 5 minutes, the voltage V1 is recorded. Then, it is discharged at 4C for 30s, and the voltage V2 is recorded. Then (V2-V1) / 4C is used to obtain the internal resistance DCR1 of the battery after the first cycle. Repeat the above steps for the same battery, and simultaneously record the internal resistance DCRn (n=1, 2, 3,,, 100) of the battery after the nth cycle. The 100 point values of DCR1, DCR2, DCR3,,, DCR100 are used as the vertical coordinates, and the corresponding SOC is used as the horizontal coordinates to obtain the curve graph of the battery discharge DCIR corresponding to the adhesive material and different SOCs.
[0428] Taking Example 1 as an example, the battery capacity retention rate test process is as follows: at 25 degrees Celsius, the battery corresponding to Example 1 is charged to 4.35V at a constant current of 1 / 3, and then charged to a current of 0.05C at a constant voltage of 4.35V, left for 5 minutes, and then discharged to 2.8V at 1 / 3C. The obtained capacity is recorded as the initial capacity C0. The above steps are repeated for the same battery, and the discharge capacity Cn of the battery after the nth cycle is recorded at the same time. Then, the battery capacity retention rate after each cycle is Pn=Cn / C0*100%. The 100 point values of P1, P2, P3,,, P100 are used as the vertical coordinates, and the corresponding number of cycles are used as the horizontal coordinates to obtain a graph of the battery capacity retention rate and the number of cycles corresponding to different combinations of adhesive materials.
[0429] As can be seen from Table 1, by comparing Examples 1, 2, 3, 4, 5, 14, 15, and 16 with Comparative Examples 4 and 5, it can be seen that when the content of the surface polymer free volume modifier is in the range of 0.5% to 16%, as the amount of the surface polymer free volume modifier added increases, there is no obvious difference in the particle size consistency coefficient σ, and the adhesion between the coating film and the electrode piece shows an increasing trend, indicating that with the increase of the surface free volume modifier, the softening temperature of the bonded microspheres decreases, which has the effect of increasing viscosity and toughness, thereby enhancing the adhesion between the coating film and the electrode piece. When the surface polymer free volume modifier content is less than 0.5%, the viscosity and toughening effects are insufficient, resulting in poor adhesion between the coating film and the electrode. When the surface polymer free volume modifier content exceeds 16%, the adhesion between the coating film and the electrode decreases instead. This is because when the surface polymer free volume modifier content exceeds a certain proportion, it affects the distribution of the microsphere particles, increases the particle size consistency coefficient σ, and widens the microsphere particle size distribution, resulting in a decrease in contact points with the electrode, a decrease in the adhesion between the coating film and the electrode, and an increase in permeability, internal resistance, and deterioration of the electrochemical performance.
[0430] From the comparison of Examples 1-27 and Comparative Examples 5-8, it can be seen that when the surface polymer free volume modifier includes any one or more of benzyl alcohol, dichloroethylene, dichloroethane, acetonitrile, ethanol, propylene glycol, 1,3-butanediol, n-butanol, tert-butanol, n-pentanol, acetone, n-butane, chloroform, dibutyl phthalate, tricresyl phosphate, ethylene carbonate, butyl ether, diethylamine, ethyl ether, n-hexane, isopropyl ether, acetic acid, ethyl acetate, etc., compared with adding a smaller amount (such as in Comparative Example 5) or adding other reagents (such as in Comparative Examples 6-8), whether there is an electrolyte or not, the above-mentioned surface polymer free volume modifier improves the adhesion between the polymer microsphere particle coating film and the electrode, and the prepared lithium ion battery exhibits good electrochemical cycle performance. When polar reagents such as N-methylpyrrolidone, N,N-dimethylformamide or dimethyl sulfoxide are used, the polymer microsphere particles can be dissolved in the above reagents, resulting in the destruction of the polymer particles. The polymer particles cannot be distributed in an island shape on the surface of the base membrane. When coated on the surface of the diaphragm, the pores of the base membrane are seriously blocked, resulting in increased permeability of the coating membrane, hindered lithium ion shuttling, increased internal resistance of the battery, and deteriorated battery performance.
[0431] Comparison of Examples 1, 11, 12, and 13 with Comparative Examples 1, 9, and 10 shows that when the particle size of the polymer microsphere particles is ≤0.4 μm, the particle size distribution consistency of the polymer microsphere particles is small, and the adhesion between the coating film and the pole piece is greatly improved, but the permeability value of the coating film increases by more than 5%, indicating that small particles significantly block the pores of the diaphragm, resulting in an increase in the internal resistance of the lithium-ion battery and deterioration of the electrochemical performance. When the particle size of the binder microsphere particles is greater than 15 μm, the particle size consistency of the polymer microsphere particles deteriorates, σ>0.3, the effective contact sites of the microsphere particles in the coating film with the components of the pole piece are reduced, the adhesion between the coating film and the pole piece is significantly reduced, and the particle size consistency deteriorates, resulting in an increase in the risk of small particle pore blocking, poor permeability of the coating film, increased internal resistance of the lithium-ion battery, and deterioration of the electrochemical cycle performance; therefore, it is preferred that the particle size distribution of the polymer microsphere particles be 0.4~15 μm.
[0432] Comparison of Examples 17, 18, 19, and 20 with Comparative Examples 2 and 3 shows that when the softening temperature of the polymer microsphere particles is lower than 30°C, the coating film has a strong adhesive force with the pole piece, and the coating film permeability value increases by 8.8%, which significantly blocks the diaphragm pores, resulting in a decrease in the permeability of the coating film, an increase in the internal resistance of the lithium-ion battery, and a deterioration in the battery cycle performance; when the softening temperature of the polymer microsphere particles is higher than 130°C, the coating film has a significantly decreased adhesive force with the pole piece, resulting in a deterioration in the lithium-ion battery cycle performance. The preferred softening temperature of the bonding microspheres is 30°C to 130°C.
[0433] By comparing Examples 1, 21, 22, 23, and 24 with Comparative Examples 11 and 12, it can be seen that when the affinity monomer ratio is less than 1%, the interaction force between the coating film bonding microspheres and the components of the electrode is weak, and the adhesion between the coating film and the electrode is weak; when the affinity monomer ratio exceeds 15%, the affinity group has a strong interaction force with the components, and the adhesion between the diaphragm and the electrode is large, but at the same time it causes the coating films to adhere to each other, and the air permeability of the coating film deteriorates, and the internal resistance of the battery increases. Therefore, the affinity monomer ratio is preferably 1% to 15%.
[0434] By comparing Examples 1, 25, 26, and 27 with Comparative Examples 11 and 13, it can be seen that when the polymer microsphere particles contain carboxyl, hydroxyl or polyvinyl alcohol side groups, the bonding force between the adhesive microsphere coating film and the electrode can be greatly improved.
[0435] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A bonding composition for battery separator, characterized in that: It comprises polymer microspheres and a modifier, wherein the modifier is a macromolecular free volume modifier on the surface of the microspheres, and the modifier accounts for 0.5-16% of the weight of the dispersion medium; the polymer microspheres contain affinity monomers, and the affinity monomers account for 1-15% of the total weight of all monomers of the polymer microspheres; The modifier is selected from at least one of benzyl alcohol, dichloroethylene, dichloroethane, acetonitrile, ethanol, glycerol, 1,3-butanediol, n-butanol, tert-butanol, n-pentanol, acetone, n-butane, chloroform, dibutyl phthalate, tricresyl phosphate, ethylene carbonate, butyl ether, diethylamine, ethyl ether, n-hexane, isopropyl ether, ethyl acetate and acetic acid; The affinity monomer has at least one of a carboxyl group, a hydroxyl group, and a polyethylene glycol side group.
2. The adhesive composition for battery separator according to claim 1, characterized in that The polymer microspheres further comprise hard monomers, soft monomers and functional monomers.
3. The adhesive composition for battery separator according to claim 2, characterized in that: The hard monomer is selected from at least one of methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, acrylonitrile, methacrylonitrile, vinyl acetate, styrene, n-butyl methacrylate, isobutyl methacrylate, tert-butyl acrylate, octadecyl acrylate, cyclohexyl methacrylate, isobornyl methacrylate, 2-phenoxyethyl acrylate, stearic methacrylate, tetrahydrofuran acrylate, isobornyl acrylate, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate and 4-tert-butylcyclohexyl acrylate; and / or, The soft monomer is selected from at least one of methyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, ethyl acrylate, n-octyl acrylate, isooctyl acrylate, dodecyl acrylate, amyl acrylate, n-hexyl acrylate, 2-hydroxypropyl methacrylate, heptyl acrylate, butyl methacrylate, lauryl methacrylate, n-octyl methacrylate, isooctyl methacrylate, hexyl methacrylate, lauric methacrylate, isodecyl methacrylate, ethoxyethoxyethyl acrylate, isodecyl acrylate, hydroxyethyl methacrylate phosphate, 2-ethylhexyl methacrylate, isononyl acrylate and propoxylated nonylphenol acrylate; and / or, The functional monomer is selected from at least one of acrylamide, N-vinyl pyrrolidone, sodium styrene sulfonate, 2-sulfonic acid ethyl methacrylate, N-(hydroxymethyl)acrylamide, N-(3-hydroxypropyl)acrylamide, N-(hydroxyethyl)acrylamide, N-(2-hydroxypropyl)methacrylamide, diacetone acrylamide, glycidyl methacrylate, vinyl siloxanes, phenyl glycidyl ether acrylate, divinylbenzene, ethylene glycol dimethacrylate, N-(isobutoxy)methacrylamide, diallyl phthalate, trimethylolpropane triacrylate, triallyl isocyanurate, allyl methacrylate, ethyl acetoacetate methacrylate, diethylene glycol diacrylate, N-ethylacrylamide, N-propylacrylamide, N-(butoxymethyl)acrylamide and N-butylacrylamide.
4. The adhesive composition for battery separator according to claim 3, characterized in that: The hard monomer accounts for 40% to 90% of the total weight of all monomers of the polymer microspheres, the soft monomer accounts for 4% to 40% of the total weight of all monomers of the polymer microspheres, and the functional monomer accounts for 1% to 20% of the total weight of all monomers of the polymer microspheres.
5. The adhesive composition for battery separator according to claim 1, characterized in that: The softening temperature of the polymer microspheres is 30°C to 130°C; and / or, The volume average particle size of the polymer microspheres is 0.4 μm to 15 μm.
6. A slurry for battery separator, characterized in that: It comprises the bonding composition according to any one of claims 1 to 5.
7. A diaphragm, characterized in that: The separator is formed using the bonding composition according to any one of claims 1 to 5 or the slurry according to claim 6 .
8. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and the separator according to claim 7, wherein the separator separates the positive electrode sheet from the negative electrode sheet.
Citation Information
Patent Citations
Composition for nonaqueous secondary battery functional layers, functional layer for nonaqueous secondary batteries, and nonaqueous secondary battery
CN109983599A
Large-particle-size core-shell polymer particle as well as preparation method and application thereof
CN115536781A
Narrow distribution diaphragm binder and preparation method thereof, lithium ion battery diaphragm and lithium ion battery
CN117060010A
Secondary particle for diaphragm coating and battery diaphragm
CN117673652A
Surface-reactive functional group-modified adhesive and adhesive tape or sheet
JP2003306660A